Analisis Financial Distress pada Perusahaan Ritel yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Fariza Alya Syalsabilla; Bakti Setyadi; Dewi Sartika; Emilia Gustini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study analyzes the financial distress conditions of retail companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024, focusing on PT Matahari Department Store Tbk (LPPF) and PT Ramayana Lestari Sentosa Tbk (RALS). The objective is to understand the potential for bankruptcy and provide information for management and investors. This study employs a descriptive qualitative approach using the Altman Z-Score method. Secondary data in the form of annual financial reports from 2020 to 2024 serve as the primary source for the Altman Z-Score model. The Altman Z-Score involves four key financial ratios: working capital to total assets (X1), retained earnings to total assets (X2), EBIT to total assets (X3), and book value of equity to book value of liabilities (X4). The research results show different dynamics between the two companies. PT Matahari Department Store Tbk (LPPF) showed significant fluctuations, briefly entering the Distress Zone in 2020 with a Z-Score of -0.19079, but recovered to the Safe Zone in 2021 and 2022, then returned to the Grey Zone in 2023, and returned to the Safe Zone in 2024. On the other hand, PT Ramayana Lestari Sentosa Tbk (RALS) demonstrated consistent financial stability in the Safe Zone throughout the 2020-2024 period, with a high Z-Score that tended to increase until 2023, indicating sustainable liquidity, operational efficiency, and profitability. The Altman Z-Score has proven effective as a tool for predicting financial distress, especially during times of economic uncertainty. RALS has demonstrated strong financial stability, while LPPF has experienced fluctuations, highlighting the importance of this tool as an early warning signal for stakeholders.